2007
DOI: 10.1080/10826080701202601
|View full text |Cite
|
Sign up to set email alerts
|

Use of Focus Groups in Developing FAS/FASD Prevention in Russia

Abstract: Fetal alcohol syndrome is a severe outcome of alcohol use during pregnancy, and the rates may be higher in countries with greater use of alcohol. To obtain information from Russian physicians (N = 23), women (N = 23), and male partners (N = 5), focus groups were conducted with 51 participants in St. Petersburg, Russia. The main objective was to determine the participants' knowledge, attitudes, and behavior related to drinking during pregnancy. Data were analyzed using ATLAS-ti 5.0. The results will be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…To our knowledge, aside from efforts to prevent fetal alcohol syndrome (36), we know of no published efforts to target alcohol interventions specifically for Russian women. Our findings provide additional insight into the characteristics and drinking behavior of women with alcohol use disorders in a highly vulnerable population of Siberian tuberculosis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, aside from efforts to prevent fetal alcohol syndrome (36), we know of no published efforts to target alcohol interventions specifically for Russian women. Our findings provide additional insight into the characteristics and drinking behavior of women with alcohol use disorders in a highly vulnerable population of Siberian tuberculosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the global rate of fetal alcohol syndrome is 1.9 per 1000 live births (35), fetal alcohol syndrome in Russia is estimated at 53 to 145 per 1000 (36). In a survey of 200 pregnant women in St. Petersburg, 60% reported drinking even when they knew they were pregnant and 35% reported drinking in the past 30 days, despite adequate knowledge of the detrimental effects of alcohol on pregnancy outcomes (31).…”
Section: Introductionmentioning
confidence: 99%
“…By profiling the context of the behaviour, and the knowledge, attitudes, beliefs, expectancies, and motivations of the target audience in terms of theoretical constructs, the effectiveness of message strategies can be strengthened. Although a number of qualitative and quantitative studies have provided insights into women's knowledge, beliefs, and attitudes with regards to alcohol use during pregnancy (Balachova, Bonner, Isurina, & Tsvetkova, 2007;Baxter, Hirokawa, Lowe, Nathan, & Pearce, 2004;Kesmodel & Kesmodel, 2002;Raymond, Beer, Glazebrook, & Sayal, 2009;Toutain, 2010), few describe formative research with the target audience that was used to develop message strategies aimed at preventing prenatal alcohol exposure (Branco & Kaskutas, 2001;Glik, Prelip, Myerson, & Eilers, 2008;Mengel, Ulione, Wedding, Jones, & Shurn, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We included eight questions about the harmfulness or advisability of drinking during pregnancy, based on our previous focus group probes (20). Responses were given on a 5-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…The only study reported that 37% of Russian women had heard about FAS (19). A pilot qualitative study conducted by our research group suggested that Russian women had limited knowledge and under-recognized the potential impact of alcohol use on pregnancy (20). The effect of knowledge and attitudes on alcohol consumption during pregnancy is not well established.…”
Section: Introductionmentioning
confidence: 99%